Life insurance demand analysis in the Czech Republic - Kábrt, Tomáš; Daňhel, Jaroslav, 1943-2025; Witzany, Jiří, 1966-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2017)
This thesis investigates the impact of demographic, economic and institutional determinants on life insurance demand in the Czech Republic between 1993 and 2015. The theoretical part derives the life insurance demand from the microeconomic theory, discusses the general characteristics of the life insurance market and its importance in the Czech Republic. It also includes a detailed research of historical publications dealing with this topic. The empirical part surveys an influence of these determinants on life insurance demand, using econometric models based on time series analysis and factor analysis. For distinguishing the short-term and long-term relationships between time series an autoregressive distributed lag model (ADL) and an error correction model (EC) were employed. It was found that an increase in average wage and banking sector size had a positive influence on life insurance demand and on the other hand an increase in young dependency ratio, old dependency ratio, interest rate and net national savings had a negative influence on life insurance demand. The number of tertiary educated people, public sector size, and consumer spending were classified as insignificant variables.
Vedoucí práce: Jaroslav Daňhel
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: finance [obor disert. práce]; disertace; dissertations